2010
DOI: 10.1152/ajpgi.00525.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ileal interposition improves glucose tolerance and insulin sensitivity in the obese Zucker rat

Abstract: The hindgut hypothesis posits improvements in Type 2 diabetes after gastric bypass surgery are due to enhanced delivery of undigested nutrients to the ileum, which increase incretin production and insulin sensitivity. The present study investigates the effect of ileal interposition (IT), surgically relocating a segment of distal ileum to the proximal jejunum, on glucose tolerance, insulin sensitivity, and glucose transport in the obese Zucker rat. Two groups of obese Zucker rats were studied: IT and sham surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 38 publications
3
44
0
2
Order By: Relevance
“…In this study, we reproducibly observed the reported effects of IT surgery in rodents: improved insulin sensitivity [31], increased L cell secretion including GLP-1 and PYY [14,32], and histological adaptation of the small intestine [32]. In addition, for the first time, we observed that circulating LPS levels decreased after IT surgery even though the surgery was performed in a non-diabetic non-obese rat model fed a normal chow diet.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, we reproducibly observed the reported effects of IT surgery in rodents: improved insulin sensitivity [31], increased L cell secretion including GLP-1 and PYY [14,32], and histological adaptation of the small intestine [32]. In addition, for the first time, we observed that circulating LPS levels decreased after IT surgery even though the surgery was performed in a non-diabetic non-obese rat model fed a normal chow diet.…”
Section: Discussionsupporting
confidence: 77%
“…In some studies with genetically obese rodent models, IT did not elicit a significant weight loss until 4 weeks [48] or 8 weeks [31] after the surgery. Notably, in our study, IT exhibited a biphasic response in food intake: an early decrease followed by a gradual recovery, which was also observed by other researchers [32,47].…”
Section: Discussionmentioning
confidence: 98%
“…Other important factors contributing to variation in these effects are the variable lengths of transposed segment and the insertion site of ileal segments. For instance, transposing a 5-10 cm of ileal segment did not have a significant impact on food intake and weight gain (38,41,43,44,117,118,120) whereas a 20-cm segment decreased intake and weight gain (20,39). SGIT is a new emerging surgical technique involving combination of SG and IT surgery in one subject (126).…”
Section: Markers Of Glucose Metabolism In Adipose Tissuementioning
confidence: 99%
“…С другой стороны, пролиферация β-клеток в островках поджелудочной железы после ИТ была Диагностика, контроль и лечение подтверждена иммуногистохимическими методами [31]. Кроме того, показано повышение потребления тканями глюкозы после ИТ [32]. Выполнение ИТ повышало уровень экспрессии мРНК инсулинозависимого транспортера глю-козы GLUT4 в скелетной мускулатуре и жировой ткани [24].…”
Section: эффекты илеотранспозиции и изменения профиля инкре-тиновunclassified